Impact of performance management system on employees’ performance: A case study of selected Banks in Nigeria - Akintola, Abiodun Sodiq (2017)
In recent times, employee performance is seen as the key to success in the performance of any organization; hence, this study is carried out to effectively study and discover the importance of performance management system on employee performance. Consequently, there is a need for the organizational performance criteria to integrate productivity, profitability, market effectiveness, customer satisfaction and also employee morale. Hence, from this viewpoint, employee performance is said to be intrinsically related to organizational performance. Thus, efficient and effective employee performance would thus positively influence the organizational performance. In order to recognize an effective and efficient organization, there is an imperative need for the organization to reconsider the ways in which they hire, train and reward their employees; hence creating an optimistic and competitive working environment. The banking sector relies heavily on the intangible asset (human capital) to succeed. Employees are the resources and assets of any organization. Therefore, it is necessary for organisations to figure out the scheme for identifying, encouraging, measuring, evaluating, improving and rewarding employees’ performance at work. In order to arrive at desired results for this research work, the qualitative research approach was adopted due to easier flexibility, mode of data collection and analysis. The data used for this research was collected for the first time via interviews conducted on relevant persons within the banking industry and transcribed accordingly. A structured interview question(s) was the research instrument used for the research and consisted of a series of questions, although, other prompts could have been considered and integrated, time was of the essence and a major constraint. The data collected was transcribed and analysed using the thematic analysis approach, the coding and mapping were done manually due to a constraint on accessing qualitative analysis software like Nvivo and EPPI reviewer amongst others. At the successful completion of the analysis of the collated data, it was observed that performance management system controls the employee performance in the sense that it gives the staff a framework for competition as well as optimism for a reward since there is an established framework that rewards or takes into account a staff’ performance. Consequently, the performance management system directly influences employee performance as it gives a drive for the employee to keep aspiring for greater heights; however, many employees do not see the practicality of the performance management system due to improper implementation. Employees, in general, believe that in the objective setting, there should be an effective inclusion of their(employees) thoughts and ideas rather than setting objectives that are one sided (regarding only organizational goals) rather than including employee aspirations. If objectives are not properly set, it can have a negative impact on the employee's performance as they would seem not to be an integral part of the organization’s operations since they are not regarded in the first place during the objective setting phase of the performance management system. Conclusively, there is a need for steps ought to be taken to make the process more practical than theoretical so as to achieve better inclusion and results. On the other hand, there is a need to keep employees on track as regards their performance rather than keeping them in the dark of what they are doing well or not.